Higher ETCOc predicts longer phototherapy treatment in neonatal hyperbilirubinemia - Zhan, Yuan-Li; Peng, Hai-Bo; Jin, Zhen-Chao; Su, Jin-Feng; Tan, Xiang-Yu; Zhao, Lu; Zhang, Lian (Frontiers in Pediatrics, 2023)
Objective: This study aimed to evaluate the predictive performance of end-tidal carbon monoxide corrected to ambient carbon monoxide (ETCOc) values phototherapy in neonates with significant hyperbilirubinemia. Methods: A prospective study was conducted on neonates with significant hyperbilirubinemia who received phototherapy between 3 and 7 days of life. The breath ETCOc and serum total bilirubin of the recruited infants were measured on admission. Results: The mean ETCOc at admission in 103 neonates with significant hyperbilirubinemia was 1.70 ppm. The neonates were categorized into two groups: phototherapy duration ≤72 h (n=87) and >72 h (n=16) groups.Infants who received phototherapy for >72 h had significantly higher ETCOc (2.45 vs. 1.60, P=0.001). The cutoff value of ETCOc on admission for predicting longer phototherapy duration was 2.4 ppm, with a sensitivity of 62.5% and specificity of 88.5%, yielding a 50% positive predictive value and a 92.7% negative predictive value. Conclusion: ETCOc on admission can help predict the duration of phototherapy in neonates with hyperbilirubinemia, facilitate clinicians to judge disease severity, and make clinical communication easier and more efficient.